2021
DOI: 10.1108/srj-12-2020-0503
|View full text |Cite
|
Sign up to set email alerts
|

The influence of family culture on the development of corporate social responsibility (CSR) initiative of immigrant enterprise: a case of Korean business in Vietnam

Abstract: PurposeThis paper aims to explore how family culture can contribute to support the development of corporate social responsibility (CSR) initiatives in a Korean immigrant enterprise in Vietnam. Design/methodology/approachThis research highlighted a critical case, in which entrepreneurs and most of the organisational members share a common family culture and the culture support management capability of an entrepreneur, during the introduction of a new organisation initiative. In addition, Bourdieu’s tripartite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Focussing on family cultural values, Nguyen et al (2021) highlighted their role in CSR initiatives in a Korean business operating in Vietnam, whereas Melo (2012) examined the influence of organisational culture on CSR performance in a sample of American companies for the period 2000-2005.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Focussing on family cultural values, Nguyen et al (2021) highlighted their role in CSR initiatives in a Korean business operating in Vietnam, whereas Melo (2012) examined the influence of organisational culture on CSR performance in a sample of American companies for the period 2000-2005.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specifically, they found that Turkish cultural and individual values differ from Western countries and that hierarchy is an important dimension. Focussing on family cultural values, Nguyen et al (2021) highlighted their role in CSR initiatives in a Korean business operating in Vietnam, whereas Melo (2012) examined the influence of organisational culture on CSR performance in a sample of American companies for the period 2000–2005.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Much research has been done on the construction of enterprise culture. The formation mechanism of the construction enterprise culture has been analyzed and several aspects of the forming process have been emphasized [1] . The construction corporate culture status of a large state-owned power company has been researched [2] .…”
Section: Introductionmentioning
confidence: 99%